2021
DOI: 10.1002/poc.4199
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic analysis of micelles formation of anionic surfactant SDS in the presence of aqueous and aqueous solution of ionic liquid 1‐butyl‐3‐methylimidazolium chloride

Abstract: In this study, the experimental conductivity, fluorescence, and UV spectroscopy study have been done for aqueous solutions of sodium dodecyl sulfate (SDS) and in aqueous ionic liquid (IL) 1‐butyl‐3‐methylimidazolium chloride [C4mim][Cl] solutions at a temperature of 298.15 K. Experimental conductivity measurement has been done at different temperatures from 298.15 to 308.15 K. Moreover, the critical micelle concentrations (CMCs) of the mentioned systems were determined by different methods; furthermore, the CM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The CMC of the surfactant is the concentration at which monomeric surfactant molecules can thermodynamically self-aggregate, forming the molecular aggregates called micelles. In other words, the CMC of surfactant is the concentration at which the micelle makes its appearance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CMC of the surfactant is the concentration at which monomeric surfactant molecules can thermodynamically self-aggregate, forming the molecular aggregates called micelles. In other words, the CMC of surfactant is the concentration at which the micelle makes its appearance.…”
Section: Resultsmentioning
confidence: 99%
“…Before above work, the experimentally obtained values of CMC for SDS in water at different temperatures were compared with some of the literature to assess the accuracy of the using determination method. The gradual decrease in the slope and a break in the plot gave the value of CMC as given in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…In recent studies it was found that imidazolium based ionic liquids with long hydrophobic chains can reduce the CMCs of SDS greatly in water by ionic interaction as well as hydrophobic–hydrophobic interactions between alkyl chains of IL and SDS surfactant. 36 Motivated with the recent report on developing the multicomponent reaction for the synthesis of pyranopyrazoles and in continuation of our on-going efforts towards the development of environmentally benign protocols for organic transformations, 37 a – d we reported herein a methodology for the synthesis of pyranopyrazole by sequential addition of aromatic aldehyde and active methylene compound (Knoevenagel condensation) followed by the addition of pyrazolone (6) derivatives in a one pot fashion at 80 °C in an essentially neutral condition comprising water–SDS–ionic liquid combo system ( Scheme 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced oil recovery (EOR) targets increasing oil mobility by changing the physical or chemical properties. Generally, the methods include injecting gas, water, or chemicals into the reservoir . Injected fluids improve the overall displacement, mobilizing and producing more trapped hydrocarbons. , Chemical flooding is a technique that employs various chemical agents such as surfactants, polymers, and alkalies.…”
Section: Introductionmentioning
confidence: 99%